Doing statistics, enacting the nation: The performative powers of categories. Issue 3 (16th February 2020) - Grommé, Francisca; Scheel, Stephan
Abstract: It has been widely acknowledged in debates about nationalism and ethnicity that identity categories used for classifying people along the lines of culture, race, and ethnicity help to enact, that is, bring into being, the collective identities they name. However, we know little about how categories acquire their performative powers. The contribution of this paper is twofold: first, it proposes a conceptual framework based on concepts and insights from science and technology studies for investigating the performative powers of statistical identity categories and possibly also other domains. Second, it demonstrates, through an empirical study of two examples from Estonian and Dutch official population statistics, that statistical identity categories enact more than the groups to which they refer. We argue that they also enact national identities and notions of national belonging of majoritarian groups in the host countries. Therefore, statistical identity categories can be used as analytical lenses to study nationalism and processes of nation‐building.